STRATEGIC ACCOUNTING MANAGEMENT IN PERUVIAN BUSINESS TEXTILES - Arrarte Mera, Raúl Alberto (2013)
This investigation made on the year 2012 with the help of the superior congress of investigation from UNMSM of Lima, Peru the explanatory documentary applicative with a qualitative approach is base of the analysis from the companies made from the national textile confections that are listed in the stock market of Lima which are compared with the emblematic companies that are in the top of the world market. Our textile industries are of great importance for been a generator of employments and foreign exchange. It´s contribution to the PBI manufacturing is situated at 11.6% take directly 215,000 persons in the fabric and spinning mills also have a textile cluster in the confections of bigger textiles in Latin American. The most important deduction is the future sector should support its suitability based on the productivity and the value-added products on the pima based of cotton and alpaca, having a competitive advantage even without competition in the world.